IMPLEMENTATION STRUB MEETING, INCENTIVE, CONFERENCE, AND EXSHIBITION (MICE) IN EVENT IMPLEMENTATION PROCESS - Pratama, Nifardi Putra; Fithroni, Hijrin (Jurnal Kesehatan Olahraga, 2019)
Abstract In Indonesia, the MICE concept has become a popular concept for event industry connoisseurs in the last 10 years. Because in the implementation of the MICE concept there are elements of marketing and promotion that can be used as a medium to disseminate the latest information in order to attract the interest of the wider community. Formulation on this problem is how concept aplication MICE and result on field in aplication event process on Karate sport event?. The purpose on this research is to known MICE application concept and field result then how long this concept get an impact for the success on sport Karate event. This research used descriptive kuantitatie method. Has a two data source on this research : 1)Data source primer get from every informan event, among others organizing comitee, athlete, athlete official/manajer, invited guess, and audiens. With total participant is 12 person. 2)Data source secuder get from real document event with file or picture graphics/sketch/desaign/layout. Research instrument using on this research is : PC, office stationery, camera, and research kuisioner angket. This research using collection and triangulasi method is observation, interview, and documentation. Based on the results of the research the researchers concluded that the application of the MICE concept during the implementation of the karate sports event had gone well in accordance with the determined plan. The concept is supported by the use of attributes and adequate equipment facilities. Although there are still shortcomings in each package of the program. Keyword : Implementation, MICE concept, event, karate sport